Microstructure and properties of in-situ Al–Si/Al2O3 composites prepared by displacement reaction - Sharma, Ashutosh; Lee, Hansung; Ahn, Byungmin (Powder Metallurgy, 2021)
In this work, we have studied the displacement reaction of Al and SiO2 powder blends by mechanical alloying (MA) for 20 h and low-temperature sintering. The microstructural evolution of powder and compacted specimens were studied by X-ray diffraction and scanning electron microscopy. The extent of the milling on the displacement reaction was studied by differential thermal analysis (DTA). The results show that the reaction between Al–SiO2 couple does not initiate after milling up to 20 h but occurs after thermal treatment of powders. DTA results indicate a lowering in the reaction temperature of Al–SiO2 couple after milling. Following the DTA results, we densified the Al–SiO2 powder compacts at 700°C to produce an in-situ Al–Si/Al2O3 composite. The physical, mechanical, and tribological performance of the composite at different milling times are also reported here.
Keywords: Differential thermal analyses (DTA); Displacement reactions; Low-temperature sintering; Microstructure and properties; Milling time; Reaction temperature; Sio2 powders; Tribological performance; displacement reaction; in-situ; Mechanical alloying; microstructure; sintering